Esquisse d’une sociolinguistique de la littérature dans le contexte algérien : enjeux théoriques et positionnements épistémologiques - Mokhtar Boughanem; Hassiba Benaldi (Multilinguales)
On the basis of Algerian research studies, this article aims to reconstitute the epistemological underpinnings of the sociolinguistics of literature, whose emergency is in full swing. First, the researcher highlights the tendency of sociolinguistics to cover heterogeneous fields, given that it raises the question of language usage. Furthermore, a quantitative approach, based on bibliometric data, was adopted to examine literature-oriented sociolinguistics in relation to academic publications that study the nexus between language and literature. Finally, the researcher broadened the analysis through a qualitative study of the content of academic work which fall under which fall within the framework of the sociolinguisitcs literature.